Patient Satisfaction after Open Rhinoseptoplasty: What Do the Statistics Say? - Jadczak, Marcin; Krzywdzińska, Sandra; Jurkiewicz, Dariusz (Otolaryngologia polska = The Polish otolaryngology, 2024)
Introduction: In its assumptions, rhinoplasty is intended to improve the aesthetics and restore normal function of the nose. In the Polish literature, a new tool has recently emerged for simultaneous assessment of the impact of rhinoseptoplasty on the external appearance and functionality of the nose. Aim: The aim of this study consisted in the surveying of patients having undergone rhinoplasty procedures using a validated and translated Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) questionnaire and the Rhinoplasty Outcome Evaluation (ROE) questionnaire to assess the functional and aesthetic outcomes of rhinoplasty. Materials and methods: A total of 106 subjects (N = 78 [73.6%] women and N = 28 men [26.4%]) aged 18 to 56 years (M = 33.99; SD = 9.77) participated in the study. The data were subjected to statistical analysis. Results: The analysis revealed significant differences between the measurements for all analyzed variables (p < 0.001). Statistically significantly lower SCHNOS scores and significantly higher ROE scores were reported in the postoperative assessments, with a strong effect for the difference of means (> 0.5). Conclusions: Properly performed rhinoplasty results in both aesthetic and, most importantly, functional improvement regardless of the patient's age and gender.